1986
DOI: 10.1002/cne.902520406
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the bowel by the precursors of enteric glia: Studies of normal and congenitally aganglionic mutant mice

Abstract: The terminal portion of the ls/ls mouse is congenitally aganglionic because the precursors of enteric neurons fail to enter this region. This animal was studied in order to gain insight into the origin of enteric glia and into the process by which the precursors of these cells colonize the gut. In control (CD-1) mice, immunoreactivity of the glial marker, glial fibrillary acidic protein, appeared for the first time in the fetal bowel at day E16 and, in adults, was much more intense within intraenteric neural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…Our study confirms the observations of Balaskas and Gabella (1998), who first reported the presence of GFAP-IR in the chick gut at early stages of development. Others have also observed GFAP-IR at late stages in the development of the chick (Payette et al, 1984) and mouse (Rothman et al, 1986). Recent observations indicate that glial markers may appear earlier in the mouse gut but still well behind the wavefront (H. Young, personal communication).…”
Section: Pattern Of Neural Crest Cell Differentiationmentioning
confidence: 94%
“…Our study confirms the observations of Balaskas and Gabella (1998), who first reported the presence of GFAP-IR in the chick gut at early stages of development. Others have also observed GFAP-IR at late stages in the development of the chick (Payette et al, 1984) and mouse (Rothman et al, 1986). Recent observations indicate that glial markers may appear earlier in the mouse gut but still well behind the wavefront (H. Young, personal communication).…”
Section: Pattern Of Neural Crest Cell Differentiationmentioning
confidence: 94%
“…Precursors of these cells are known to reach developing gut at as early as 9 to 10 dpc (Rothman et al, 1986) and at around 12.5 dpc lacZ expressing cells appeared. This suggests that neural crest precursors develop to produce SLF after reaching the developing gut.…”
Section: Discussionmentioning
confidence: 99%
“…These cells colonize the mouse embryonic gut at E9.0 and, when cultured in vitro, give rise to both neurons and glial cells (Rothman et al, 1986). However, during development, enteric neurons appear prior to EGCs as evidenced by the detection of specific markers for both cell types (Rothman and Gershon, 1982;Rothman et al, 1986), and the intrinsic and environmental signals involved in the commitment of precursor cells in the neuronal or glial lineages remain to be elucidated.…”
Section: Localization and Phenotypic Characteristics Of Egcmentioning
confidence: 99%
“…EGCs could therefore contribute to the development of the enteric neuronal network (Bä r et al, 1997;Gershon, 1999) and to neuroprotection. However, EGCs are not the primary source of GDNF in the developing gut as GDNF is expressed as early as E9.0 in the mouse gut (Hellmich et al, 1996), although differentiated EGCs first appear at E16 (Rothman et al, 1986).…”
Section: Neuroprotective and Neuromodulatory Functions Of Egcmentioning
confidence: 99%